The role of platelets, neutrophils and endothelium in COVID-19 infection. Issue 8 (3rd August 2022) - Falcinelli, E.; Petito, E.; Gresele, P.
ABSTRACT: Introduction: COVID-19 is associated to an increased risk of thrombosis, as a result of a complex process that involves the activation of vascular and circulating cells, the release of soluble inflammatory and thrombotic mediators and blood clotting activation. Areas covered: This article reviews the pathophysiological role of platelets, neutrophils, and the endothelium, and of their interactions, in the thrombotic complications of COVID-19 patients, and the current and future therapeutic approaches targeting these cell types. Expert opinion: Virus-induced platelet, neutrophil, and endothelial cell changes are crucial triggers of the thrombotic complications and of the adverse evolution of COVID-19. Both the direct interaction with the virus and the associated cytokine storm concur to trigger cell activation in a classical thromboinflammatory vicious circle. Although heparin has proven to be an effective prophylactic and therapeutic weapon for the prevention and treatment of COVID-19-associated thrombosis, it acts downstream of the cascade of events triggered by SARS-CoV-2. The identification of specific molecular targets interrupting the thromboinflammatory cascade upstream, and more specifically acting either on the interaction of SARS-CoV-2 with blood and vascular cells or on the specific signaling mechanisms associated with their COVID-19-associated activation, might theoretically offer greater protection with potentially lesser side effects.